Determination of lead in aqueous solutions using resonant surface-enhanced LIBS. Issue 11 (11th October 2021) - Liu, Kun; Tang, Zhiyang; Zhou, Ran; Zhang, Wen; Li, Qingzhou; Zhu, Chenwei; He, Chao; Liu, Ke; Li, Xiangyou
Abstract : Resonant surface-enhanced LIBS(R-SENLIBS) was proposed to improve the LoD of lead in aqueous solutions. Abstract : The toxicity of lead (Pb) in water is known to affect cellular components, enzymatic machinery and genomic instability. The detection of lead in water is of great significance. In this study, a method called resonant surface-enhanced LIBS (R-SENLIBS) was proposed to improve the LoD of lead in aqueous solutions. RLIBS was coupled with SENLIBS in this method. Lead in aqueous solutions was compounded in a concentration range of 0.01 to 0.6 mg L −1 . The calibration curve of these solutions was built. The value of coefficients of determination ( R 2 ) was as high as 0.996 and an LoD of 0.0021 mg L −1 was achieved for the linear calibration range of 0.01 to 0.2 mg L −1 . Compared to previously published studies involving lead detection by LIBS, the analysis capability of R-SENLIBS proposed in this study is superior to that of those approaches in these studies. Moreover, the calibration range and LoD in this study meet the drinking water sanitation standard of China (0.01 mg L −1 for Pb, GB5749-2006) and WHO guidelines on lead. Trueness evaluation was carried out by spike and recovery experiments in a real sample of tap water, resulting in recovery values in the range of 101–110%. Spectral comparison indicated that impurities in the substrate and real aqueous solution had little influence on the lead signal in R-SENLIBS. The enhancement mechanism of R-SNELIBS was discussed. The on-resonance excitation and stratified structure of the sample are the two main reasons that lead to a valid signal of Pb. In summary, the method proposed in this study can be an alternative for lead analysis in drinking-water monitoring.